Kontribusi Pelaksanaan Supervisi Akademik Oleh Kepala Sekolah Dan Kompetensi Pedagogik Terhadap Kinerja Guru - Novebri Novebri (STAIN Madina Press, 2020)
This research was a case where the result of observation researcher at Elementary School in Kecamatan Enam Lingkung that shows the low level of teacher performance. Many factors that affect teacher performances among which are academic supervision and pedagogical competence. The purpose of this research are to know about: (1) contribution of academic supervision to teacher performance, (2) contribution of pedagogical competence to teachers performance, and (3) contribution of academic supervision and pedagogical competence are jointly to teachers performance. The method of this study is quantitative research with 157 teachers. Sample in this research has taken by the use stratified proportional random sampling method, total sample in this research are 78 teachers. Instrument in this research using questionnaire and test. The results of the analysis data show that (1) academic supervision contributes significantly to teachers of 44%, (2) pedagogical competence contributes significantly to teachers 12,1 %, and (3) academic supervision and pedagogical competence are jointly make a significant contribution to teachers performance of 44,2%, so the conclusion of this research are that hypothesis acceptable empirically and academic supervision and pedagogical competence variable are two factors that contribute to the teacher performance and 55,8% of the remaining influence by another factors.